PENERAPAN TEKNIK INFORMATION GAP UNTUK MENINGKATKAN KEMAMPUAN BERBICARA SISWA KELAS DUA DI SMA NEGERI 11 PEKANBARU - Novi Fatrina Novi Fatrina; Mahdum Mahdum '; Desri Maria Sumbayak Maria Sumbayak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on the writer’s small observation in the process of teaching and learning English and an interview with one of the English teachers in SMA Negeri 11 Pekanbaru, most of students faced difficulties in speaking English and their speaking score were lower than KKM so that the teacher needed to find the appropriate teaching technique to improve their speaking ability. Therefore, this research was aimed to find out whether the application of Information Gap technique could improve the speaking skill of the students. The participants were 28 students of XI IPA 3 class. This research was conducted in two cycles, three meetings in each cycle. The instruments of this study were collected quantitatively by asking the students to tell story based on the picture sequences in the pre test, post test 1, post test 2 and qualitatively by asking the collaborator to fill the observation sheet and field note. The writer used the score in Pre-test as a guidance for her to conduct this research. The research finding showed that the application of information gap as the teaching technique could improve students’ speaking ability both at the first cycle and second cycle. The finding also proved that the students’ average score was only 68.10 in the pre-test, then it improved to 73.48 in the post-test 1, and finally improved to 82.10 in the post-test 2, it could increase students’ interest and motivation to speak and share ideas with their partners in pairs or groups since the core of information gap was a collaboration between groups or pairs, and it also improve students’ ability to speak English in terms of grammar, vocabulary, pronunciation, fluency, and comprehension.Keywords: information gap technique, students’ speaking ability, picture sequences